Influence education health using bugis language to knowledge about exclusive breastfeeding in post partum mother - Darwin, Devi; Yulianti . N; Irmayanti; Asmiranda (Jurnal Konseling dan Pendidikan, 2025)
Breast milk is a type of milk produced by mothers after giving birth which contains very complete nutrition and is needed by babies to grow and develop. develop. Approach Which effective in increase giving breast milk exclusive is by providing health education to mothers, either before or after birth. An effective way make it easier delivery message to Mother used health education with Bugis language to improve understanding and acceptance of health messages. Research This aiming For Analyzing the influence health education using Bugis language on knowledge about exclusive breastfeeding in postpartum mothers at the UPTD Ponrang Health Center. This type of research is quantitative with a pre-experimental design using One Group Pre test – Post test design. The sampling technique used in this study is non probability sampling by accident sampling. Tool The research used a questionnaire. The analysis technique used one of the non-parametric statistical tests, namely the Wilcoxon Match Pair Test. The results of the Wilcoxon test obtained a p value of 0.000 smaller than the α value of 0.05 so it was concluded that there was an influence of health education using the Bugis language on knowledge about Exclusive Breastfeeding in postpartum mothers at the Ponrang Health Center UPTD. Important for Mother post partum For actively seeking information health related to their pregnancy. They should actively participate in health education programs provided by local health centers or health institutions.